The Antitumor Effect of Heparin is not Mediated by Direct NK Cell Activation - Gustavo R. Rossi (Journal of Clinical Medicine, 2020)
Natural killer (NK) cells are innate lymphocytes responsible for the elimination of infected or transformed cells. The activation or inhibition of NK cells is determined by the balance of target cell ligand recognition by stimulatory and inhibitory receptors on their surface. Previous reports have suggested that the glycosaminoglycan heparin is a ligand for the natural cytotoxicity receptors NKp30, NKp44 (human), and NKp46 (both human and mouse). However, the effects of heparin on NK cell homeostasis and function remain unclear. Here, we show that heparin does not enhance NK cell proliferation or killing through NK cell activation. Alternatively, in mice models, heparin promoted NK cell survival in vitro and controlled B16-F10 melanoma metastasis development in vivo. In human NK cells, heparin promisingly increased interferon (IFN)-γ production in synergy with IL-12, although the mechanism remains elusive. Our data showed that heparin is not able to increase NK cell cytotoxicity.